2020
DOI: 10.3389/fmicb.2020.589640
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms and Promising Applications of Quorum Sensing-Inhibiting Agents in Control of Bacterial Biofilm Formation

Abstract: A biofilm is an assemblage of microbial cells attached to a surface and encapsulated in an extracellular polymeric substance (EPS) matrix. The formation of a biofilm is one of the important mechanisms of bacterial resistance, which not only leads to hard-to-control bacterial infections in humans and animals but also enables bacteria to be a major problem in various fields, such as food processing, wastewater treatment and metalworking. Quorum sensing (QS) is a bacterial cell-to-cell communication process that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 115 publications
0
106
0
1
Order By: Relevance
“…Notably, those differentially expressed proteins associated with the quorum sensing (QS) system, including the downregulated proteins of RhlR, PqsH, LecA, LasB, and PhnB, and the upregulated proteins of LasI and RhlA were found, as shown in the pae02024 quorum sensing map ( Supplementary Figure S8 ). The QS network of P. aeruginosa is a multi-layered hierarchy composed of at least four interconnected signal mechanisms, including Las, Rhl, Pqs, and Iqs systems ( Lee and Zhang, 2015 ; Turkina and Vikström, 2019 ; Zhou et al, 2020 ). These differentially expressed QS proteins are mainly involved in regulating the production of rhamnolipid and lectin A ( Diggle et al, 2006 ; Soto-Aceves et al, 2021 ) and play a role in promoting the formation and maintenance of the mature structure of biofilm ( Fila et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, those differentially expressed proteins associated with the quorum sensing (QS) system, including the downregulated proteins of RhlR, PqsH, LecA, LasB, and PhnB, and the upregulated proteins of LasI and RhlA were found, as shown in the pae02024 quorum sensing map ( Supplementary Figure S8 ). The QS network of P. aeruginosa is a multi-layered hierarchy composed of at least four interconnected signal mechanisms, including Las, Rhl, Pqs, and Iqs systems ( Lee and Zhang, 2015 ; Turkina and Vikström, 2019 ; Zhou et al, 2020 ). These differentially expressed QS proteins are mainly involved in regulating the production of rhamnolipid and lectin A ( Diggle et al, 2006 ; Soto-Aceves et al, 2021 ) and play a role in promoting the formation and maintenance of the mature structure of biofilm ( Fila et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Former studies demonstrated that gallic acid inhibited biofilm formation in Staphylococcus aureus (Luís et al, 2014), P. aeruginosa (Zhang et al, 2020), E. coli, and Streptococcus mutans (Shao et al, 2015). Likewise, the antibiofilm effect of cinnamic acid derivatives was recognized in recent studies (Zhou et al, 2020). Various mechanisms have been proposed to justify the antibiofilm activities of phenolic compounds including gallic and cinnamic acid derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…; (3) interfere with the signal receptors using AI antagonists; (4) interfere with the response regulators thus disturbing signaling cascade; (5) reduce the extracellular AIs accumulation by inhibiting AIs efflux hence inhibited cell-to-cell signaling. 82,90 Fig. 12 Some reported substituents as head group replacements in AHL to obtain QSI.…”
Section: Targeting Quorum Sensingmentioning
confidence: 99%
“…The ideal cellular effect of QSI targeting LasR and/or RhlR would be the reduction in the production of virulence factors (such as elastase, hydrogen cyanide, pyocyanin, pyoverdin, rhamnolipid or alkaline protease) as well as the attenuation of biolm formation. [82][83][84][85][86][87][88][89][90] The following section provides a detailed but not exhaustive overview of the structures covered by the synthetic QSI that interferes with AHL signals. Generally, compounds targeting LasR and Rh1R can be divided into two categories: structural mimics of AHL and structurally unrelated substances.…”
Section: Targeting Quorum Sensingmentioning
confidence: 99%